FROM OVEN TO ONLINE: A PARTICIPATORY ACTION RESEARCH ON ADOPT A BUSINESS SOLUTIONS FOR A BAKERY - Madarasinghe, H.V.; Dilrukshi, R.M.U.E.; Senevirathna, M.G.P.N.; Basnayaka, T.K.; Malshani, B.R.; Dilogini, S. (University of Vavuniya, 2025)
This research explores how basic digital branding tools, including Facebook, QR codes, and creative contents, allow small food businesses to increase their visibility and engagement with customers. Using a Participatory Action Research (PAR) approach, the project developed basic low-cost digital solutions in collaboration with Ingaran Bakery, a local Micro, Small and Medium Enterprise (MSME) in Jaffna. Over a four-month period, a team of undergraduate students of department of marketing and the bakery owner collaborated to assess the bak R code-based advertisements. Through the PAR cycles, students identified, implemented (Facebook page, QR code, logo design, contents creation), monitored (reach, engagement rates), and refined (content strategies via owner input). The project emphasized co marketing. The introduction of digital platforms such as Facebook significantly increased Ingara visibility in the local online community. Within a few weeks, the Facebook page gained followers and engagement through attractive post designs and promotions, while customer inquiries and comments began coming in via Facebook Messenger, improving overall communication. The owner, who was initially unfamiliar with social media tools, gradually became confident in managing basic posts and interacting with customers, and as a result, the bakery experienced a significant increase in both walk-in customers and brand recall. The project helped empower the bakery owner to manage their own digital marketing, and the study shows that a small number of digital tools can deliver significant branding effects, especially when combined with substantial and consistent content and visual storytelling. The study proves how students can effectively serve as digital change agents for small businesses, while maintaining the identity of relevant MSME. The project recommends using the student-led branding model more widely by creating easy-to-use design toolkits supported by businesses a businesses. These low-cost ideas could also get a boost from micro-influencers who promote online.
Keywords: Adopt a Business; Digital Change Agents; Micro; Small and Medium Enterprise (MSME); Participatory Action Research (PAR); Social Media Marketing